Novel Anticancer Agents: Strategies for Discovery and Clinical Testing - Alex A Adjei [ Editor ] (Elsevier Academic Press, 2006)
This book offers pertinent basic science information on strategies used for the rational design and discovery of novel anticancer agents, and, in addition, translational studies involving clinical trial design and execution with these novel, mostly cytostatic agents. This book covers basic science strategies that are being used in drug discovery and preclinical evaluation focused on novel molecular targets, as well as clinical trial methodology including clinical pharmacokinetics and imaging to address issues of efficacy evaluation of the new, relatively non-cytotoxic anticancer agents.At present, there is no book that provides such an integration of basic and clinical studies of novel anticancer agents, covering both drug discovery and translational research extensively.